Mechanical power, energy cost and performance comparison between two ultra-cycling world records: a case study - Forte, P.; Thuany, M.; Weiss, K.; Nikolaidis, P. T.; Cuk, I.; Sousa, C. V.; Andrade, M. S.; Knechtle, B. (Trends in Sport Sciences, 2026)
Introduction: Ultra-cycling is a complex sport and a variation of individual characteristics.